2009
DOI: 10.5194/acp-9-9197-2009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of scintillation on quality of ozone monitoring by GOMOS

Abstract: Abstract. Stellar light passing through the Earth atmosphere is affected by refractive effects, which should be taken into account in retrievals from stellar occultation measurements. Scintillation caused by air density irregularities is a nuisance for retrievals of atmospheric composition. In this paper, we consider the influence of scintillation on stellar occultation measurements and on the quality of ozone retrievals from these measurements, based on experience of the GOMOS (Global Ozone Monitoring by Occu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 13 publications
0
65
1
3
Order By: Relevance
“…Other GOMOS self-collocations (less than 30 per year) are for different stars in successive orbits (Guirlet et al, ) in years 2002(Guirlet et al, -2004 The estimated retrieval uncertainty for GOMOS ozone is small in the stratosphere; for very bright stars it is ∼ 0.5-2 % (Sofieva et al, 2009;Tamminen et al, 2010). For an experimental estimation of precision in such occultations by the Fioletov method, a very large number of collocations with measurements from another instrument is needed, even in regions of low natural variability (Appendix B).…”
Section: Specifics Of Gomos Measurements and Challenges For Precisionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other GOMOS self-collocations (less than 30 per year) are for different stars in successive orbits (Guirlet et al, ) in years 2002(Guirlet et al, -2004 The estimated retrieval uncertainty for GOMOS ozone is small in the stratosphere; for very bright stars it is ∼ 0.5-2 % (Sofieva et al, 2009;Tamminen et al, 2010). For an experimental estimation of precision in such occultations by the Fioletov method, a very large number of collocations with measurements from another instrument is needed, even in regions of low natural variability (Appendix B).…”
Section: Specifics Of Gomos Measurements and Challenges For Precisionmentioning
confidence: 99%
“…The residual scintillation error (i.e., the uncertainty due to incomplete scintillation correction) has been characterized in depth (Sofieva et al, 2009) and has been included in the inversion algorithm . The residual scintillation error depends on the obliquity of occultation; it vanishes for vertical (in-orbital-plane) occultations.…”
Section: Outlines Of Gomos Precision Derivation and Characterization mentioning
confidence: 99%
See 1 more Smart Citation
“…9). This causes about 0.5-1.5% additional error in the ozone retrievals at the altitude range of 20-45 km (Sofieva et al, 2009). The modelling error from the imperfect scintillation correction can be taken into account in the spectral inversion by introducing a wavelength correlated modelling error.…”
Section: Scintillation -Dilution Correctionmentioning
confidence: 99%
“…In the GOMOS retrievals, the perturbations in the stellar flux caused by scintillations are corrected by using additional scintillation measurements by the fast photometer operating in low-absorption wavelength region (Dalaudier et al, 2001;Sofieva et al, 2009). The quality of the scintillation correction and its limitations are discussed in Sofieva et al (2009) where it was shown that the applied scintillation correction removes significant part of the perturbations in the recorded stellar flux, but it is not able to remove scintillations generated by the isotropic turbulence.…”
Section: Scintillation -Dilution Correctionmentioning
confidence: 99%